Self-efficacy as a key psychological predictor of learning independence among students in an integrated Islamic elementary school - Susantie Susantie; Lucia Rini Sugiarti; Erwin Erlangga (Institute of Computer Science (IOCS), 2026)
As the foundation for lifelong learning, independent learning is an important psychological skill that must be developed from elementary school. The internal component of self-efficacy is crucial for enhancing independent learning. The purpose of this study was to investigate how self-efficacy influences elementary school students' ability to learn independently. A total of 87 fifth-grade students selected from the overall sample were included in a quantitative correlational design. Validated measures of independent learning and self-efficacy were used to collect data. Independent learning and self-efficacy were found to be significantly positively correlated based on Pearson correlation analysis (r = 0.523, p < 0.01). Simple linear regression analysis showed that self-efficacy explained 27.4% of the variation in independent learning (R2 = 0.274). These findings indicate that students with higher self-efficacy tend to demonstrate greater ability to manage and regulate their learning independently. The study highlights the importance of strengthening self-efficacy as a psychological foundation for promoting learning independence from an early educational stage